Understanding the Crime Gap: Violence and Inequality in an American City. (December 2018) - Papachristos, Andrew V.; Brazil, Noli; Cheng, Tony
The United States has experienced an unprecedented decline in violent crime over the last two decades. Throughout this decline, however, violent crime continued to concentrate in socially and economically disadvantaged urban neighborhoods. Using detailed homicide records from 1990 to 2010, this study examines the spatial patterning of violent crime in Chicago to determine whether or not all neighborhoods experienced decreases in violence. We find that while in absolute terms nearly all neighborhoods in the city benefited from reductions in homicide, relative inequality in crime between the city's safest and most dangerous neighborhoods actually increased by 10 percent. This increase was driven by a greater rate of decline in the city's safest neighborhoods. This crime gap can be partly attributed to the decreasing association between concentrated disadvantage and homicide in the safest neighborhoods. We also find that the decline did not significantly alter the spatial distribution of crime, as homicides remained concentrated in the initially most dangerous neighborhoods and their adjacent areas.